Physico-chemical and Antioxidant Properties of Moringa oleifera Seed Oil - Ogbunugafor, H.A.; Eneh, F.U.; Ozumba, A.N.; Igwo-Ezikpe, M.N.; Okpuzor, J.; Igwilo, I.O.; Adenekan, S.O.; Onyekwelu, O.A. (Pakistan Journal of Nutrition, 2011)
Oil was extracted from Moringa oleifera Lam (Moringaceae) seeds collected from Enugu, South-East Nigeria and evaluate its physico-chemical and antioxidant properties in comparism to palm oil. M. oleifera seeds gave oil yield of 41.47%. Refractive index, melting point (oC) and acid value (mg KOH g-1) of M. oleifera oil were 1.471±0.00, 28±0.00, 3.80±0.28 while palm oil had 1.473±0.00, 31±0.00, 6.20±0.35 respectively. Similarly, iodine (I2 100 g-1), saponification (mg KOH g-1) and peroxide (mMol kg-1) values obtained for M. oleifera oil were 85.30±0.25, 171.90±0.56 and 8.10±0.07 whereas palm oil had 34.70±0.13, 210.50±0.00 and 13.40±0.28 respectively. Total phenol (mg Gallic Acid Equivalent g-1), total flavonoids (mg Rutin Equivalent g-1) and total antioxidant capacity (mg Ascorbic Acid Equivalent g-1) were 40.17±0.01, 18.24±0.01, 37.94±0.02 for M. oleifera oil and 62.32±0.04, 33.13±0.03, 68.27±0.02 for palm oil respectively. M. oleifera oil and palm oil showed a concentration dependent DPPH free radical scavenging and reducing power capabilities. This study has shown that Moringa Oleifera gave high oil yield, which has good antioxidant capacity with potential for industrial, nutritional and health applications, therefore large scale cultivation of this economic plant could be used as poverty alleviation strategy in Nigeria.